ABA Is Involved in Regulation of Cold Stress Response in Bermudagrass - Huang, Xuebing; Shi, Haiyan; Hu, Zhengrong; Liu, Ao; Amombo, Erick; Chen, Liang; Fu, Jinmin (Frontiers in Plant Science, 2017)
As a representative warm-season grass, Bermudagrass [Cynodon dactylon (L). Pers.] is widely used in turf systems. However, low temperature remarkably limits its growth and distribution. ABA is a crucial phytohormone that has been reported to regulate much important physiological and biochemical processes in plants under abiotic stress. Therefore, the objective of this study was to figure out the effects of ABA on the cold-sensitive (S) and cold-resistant (R) Bermudagrass genotypes response to cold stress. In this study, the plants were treated with 100 µM ABA solution and exposed to 4°C temperature. After 7 days of cold treatment, the electrolyte leakage (EL), malonaldehyde (MDA) and H2O2 content were significantly increased in both genotypes compared with control condition, and these values were higher in R genotype than those of S genotype, respectively. By contrast, exogenous ABA application decreased the electrolyte leakage (EL), malonaldehyde (MDA) and H2O2 content in both genotypes compared with those plants without ABA treatment under cold treatment condition. In addition, exogenous ABA application increased the levels of chlorophyll a fluorescence transient curve for both genotypes, and it was higher in R genotype than that of S genotype. Analysis of photosynthetic fluorescence parameters revealed that ABA treatment improved the performance of photosystem II under cold condition, particularly for the R genotype. Moreover, cold stress significantly increased δ13C values for both genotypes, while it was alleviated by exogenous ABA. In summary, exogenous ABA application enhanced cold resistance of both genotypes by maintaining cell membrane stability, improving the process of photosystem II, increasing carbon isotopic fractionation under cold stress, and more prominently in R genotype compared with S genotype.